Thermal Performance Enhancement of the Mixed Convection between two Parallel Plates by using Triangular Ribs - K.A. Jehhef; F.A. Badawy; A.A. Hussein (International Journal of Applied Mechanics and Engineering, 2021)
This paper aims to investigate the mixed convection between two parallel plates of a vertical channel, in the presence of a triangular rib. The non-stationary Navier-Stokes equations were solved numerically in a two-dimensional formulation for the low Reynolds number for the laminar air flow regime. Six triangular ribs heat-generating elements were located equidistantly on the heated wall. The ratio of the ribs to the channel width is varied ( h / H = 0.1, 0.2, 0.3 and 0.4) to study the effect of ribs height effects, the ratio of the channel width to the ribs height is fixed constant at ( H / w = 2 ) and the ratio of the channel height to the ribs pitch is fixed at ( W/p=10 ). The influence of the Reynolds number that ranged from 68 to 340 and the Grashof number that ranged from 6.6 ×103 to 2.6 ×104 as well as the Richardson number chosen ( 1.4, 0.7, 0.4 and 0.2 ) is studied. The numerical results are summarized and presented as the profile of the Nusselt number, the coefficient of friction, and the thermal enhancement factor. The contribution of forced and free convection to the total heat transfer is analyzed. Similar and distinctive features of the behavior of the local and averaged heat transfer with the variation of thermal gas dynamic and geometric parameters are investigated in this paper. The results showed that the Nusselt number and friction factor increased by using the attached triangular ribs, especially when using the downstream ribs. Also, the results revealed that the Nusselt number increased by increasing the ratio of the ribs to the channel width.